The Role of Human Resource Management in Improving Work-Life Balance within Organizations - Yatminiwati, Mimin; Hidayat, Zainul (Jurnal Ilmu Manajemen Advantage, 2025)
The purpose of this research is to analyze the role of human resource management in improving work-life balance. In this study, the researcher uses a literature analysis method to gain insights into the research topic being studied. The role of human resources is to increase the contribution of human resources (employees) in the organization. To achieve this goal, human resources must be evaluated comprehensively and corrective actions must be taken whenever there are unsatisfactory results or significant changes in the growth of an institution. Human resource management plays a crucial role in achieving organizational goals. Human resource management is essential for the success of an organization. Human Resource Management also manages conflicts, improves internal communication, and creates an inclusive and performance-oriented work culture, and acts as a catalyst in achieving organizational goals. Therefore, human resource management plays a vital role in ensuring the success and sustainability of an organization by helping to manage human resources effectively, thereby creating a productive, innovative, and sustainable work environment. The results of this study show that Human Resource Management can play a crucial role in improving work-life balance in organizations by developing flexible work policies, managing workload, developing wellness programs, facilitating effective communication, and developing organizational culture.